Pengembangan Konteks Keluaran 20:1-11 Dalam Imamat 19:1-8 - Lidia Yulianti; Penina Itlay; Mikhael Zelod Natanel (KAPATA: Jurnal Teologi dan Pendidikan Kristen, 2022)
Leviticus is difficult for Christians to interpret today. The book is often considered irrelevant to the life of the church today. This causes some Christians do not study Leviticus carefully. Chapter 19 is the main idea of the book of Leviticus. A careful examination at Leviticus 19:1-8 points to the fact that the passage contains an intertextual connection with Exodus 20:1-11. This article records an intertextual analysis of Leviticus 19:1-8 with Exodus 20:1-11. The form of the intertextual relationship between the two texts is allusion. Therefore, the writer uses the allusive interpretation technique to find the meaning of the intertextual relationship between the two texts. The regulations in Leviticus 19: 1-8 are to be understood in light of God's covenant with Israel. The rules that God revealed to Israel in Leviticus 19: 1-8 are God's way of maintaining His relationship with Israel. Christians can study this passage to find principles for keeping a holy life before God.